MORNING PHYSICAL EXERCISES AS THE INITIAL STAGE OF A HEALTHY LIFESTYLE (The Conference Hub, 2025)
In the modern era, characterized by rapid urbanization, sedentary behavior, and widespread technological dependence, the concept of a healthy lifestyle is increasingly being recognized as a strategic national priority. At the foundation of such a lifestyle lies daily morning physical activity, which functions as both a physiological activator and a behavioral primer that sets the tone for the entire day. Morning exercise (commonly referred to as morning gymnastics or morning workout) is not simply a routine—it is a regulatory mechanism that synchronizes human biological rhythms, stimulates functional systems, enhances cognitive readiness, and establishes a psychological orientation toward health-preserving behaviors.